2011
DOI: 10.4161/hv.7.2.14003
|View full text |Cite
|
Sign up to set email alerts
|

The immunogenicity and safety of vaccination with purified Vero cell rabies vaccine (PVRV) in China under a 2-1-1 regimen

Abstract: 2 Because rabies is fatal in nearly 100% of cases, post-exposure prophylaxis (PEP) is among the most important measures for its prevention and control. For people exposed to rabies virus carrying animals, PEP consists of wound cleansing, rabies vaccination and passive immunization with rabies immune globulin, if necessary.3 A reported 12-15 million people in China receive PEP each year, which results in direct medical expenses around $280 million to $310 million. 4 The intramuscular PEP recommended by the Worl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
37
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 3 publications
9
37
0
Order By: Relevance
“…In a study conducted in China using locally produced PVRV administered under the 2-1-1 regimen similar anti-body levels were reported [8]. Furthermore, Liu et al [8] did not observe a significant difference in antibody level between subjects undergoing vaccination under Essen protocol with those of Zagreb method. In line with the WHO recommendations, antibody ti-ters of ≥0.5 IU/ml was considered indicative of seroconversion and in this study, this value was almost 3 times higher; therefore seroconversion was 100% by day 21.…”
Section: Discussionmentioning
confidence: 59%
See 4 more Smart Citations
“…In a study conducted in China using locally produced PVRV administered under the 2-1-1 regimen similar anti-body levels were reported [8]. Furthermore, Liu et al [8] did not observe a significant difference in antibody level between subjects undergoing vaccination under Essen protocol with those of Zagreb method. In line with the WHO recommendations, antibody ti-ters of ≥0.5 IU/ml was considered indicative of seroconversion and in this study, this value was almost 3 times higher; therefore seroconversion was 100% by day 21.…”
Section: Discussionmentioning
confidence: 59%
“…Zagreb regimen is a shortened version of Essen treatment, reducing the number of injections, visits and duration of the treatment, making it economically more acceptable. Clinical trials and epidemiological studies have demonstrated the efficacy of Zagreb protocol [8,10,12] All patients were negative for anti-rabies antibody prior to treatment (D0) but subsequently showed significant increase in anti-rabies antibody on day 21 (Table 1). In a study conducted in China using locally produced PVRV administered under the 2-1-1 regimen similar anti-body levels were reported [8].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations